Studying the relationship between students' self-efficacy and social adaptation - Ulziibayar, Namier (Lavai - International Journal of Education, 2023)
This study examined the relationship between student self-efficacy and social adaptability. Our research is innovative in that it examines the relationship between social adaptability and self-efficacy, which is one of the soft skills considered to be important skills of the 21st century. 2,713 students from five universities of Inner Mongolians participated in the study. According to the results of the research, the student's social adaptation in 7 parameters (learning, "I" with people, professional choice, self-reliance in life, environment, somatic mental characteristics) is above average or good (M=3.68), self-efficacy is above average for all students (M=2.58). Also, according to the results of the T-test analysis of self-efficacy, there is a difference between genders (p = 0.001), i.e. male students have higher self-efficacy and social adaptation. The total score of social adaptation of male and female students (p = 0.049) and their environment overall acceptance (p=.001) is different depending on gender, the total score of social adaptation (p=.008) and learning adaptability (p=.000), adaptability with people (p= .010), adaptability of "I" (p=.000), adaptability to career choice (p=.009) are different to a certain extent. Also, social adaptation and self-efficacy have a moderately positive correlation (r=.329), and self-efficacy affects social adaptation by 10.8% (ΔR² = 0.108). Оюутны өөрийн үр дүнт шинж болон нийгмийн дасан зохицохуйн хамаарлыг судалсан нь Хураангуй: Энэхүү судалгаа нь оюутны өөрийн үр дүнт шинж болон нийгмийн дасан зохицохуйн хамаарлыг судалсан. Бидний судалгаа нь XXI зууны чухал чадварт тооцогдож буй зөөлөн ур чадварын нэг болох нийгмийн дасан зохицохуй болон өөрийн үр дүнт шинжийн хамаарлыг судалсан нь шинэлэг талтай. Тус судалгаанд ӨМӨЗО-ы таван их сургуулийн 2713 оюутан оролцсон. Судалгааны үр дүнд оюутны нийгмийн дасан зохицохуй нь долоон үзүүлэлтийн (суралцахуйн, хүмүүстэй, ”Би”-ийн, мэргэжил сонголтын, амьдралд бие даах, хүрээлэн буй орчинд, соматик сэтгэцийн шинж) хувьд дундаж нь (M=3,68) дунджаас дээгүүр буюу сайн , өөрийн үр дүнт шинж нь нийт оюутнуудын хувьд (M=2.58) дунджаас дээгүүр байна. Мөн өөрийн үр дүнт шинжийн Т тестийн шинжилгээний үр дүнд хүйсийн хувьд ялгаатай (p = 0.001) буюу эрэгтэй оюутнуудын өөрийн үр дүнт шинж өндөр, нийгмийн дасан зохицохуйн хувьд Эрэгтэй, эмэгтэй оюутнуудын нийгмийн дасан зохицохуйн нийт оноо (p=.049) болон хүрээлэн буй орчноо цогцоор нь хүлээн зөвшөөрөх чадвар (p =.001) нь хүйсээс хамааран ялгаатай, хот, хөдөөгөөс шалтгаалаан нийгмийн дасан зохицохуйн нийт оноо (p =.008) болон суралцахуйн дасан зохицох чадвар (p=.000), хүмүүстэй дасан зохицох чадвар (p =.010), “Би”-ийн дасан зохицох чадвар(p=.000), мэргэжил сонголтдоо дасан зохицох чадвар (p=.009) зэрэг нь тодорхой хэмжээнд тус тус ялгаатай байна. Мөн нийгмийн дасан зохицохуй болон өөрийн үр дүнт шинж нь (r =.329) дунд зэрэг эерэг хамааралтай , өөрийн үр дүнт шинж нь нийгмийн дасан зохицохуйд 10.8% (ΔR² = 0.108) -р нөлөөлж байна. Түлхүүр үг: оюутан, өөрийн үр дүнт шинж, нийгмийн дасан зохицохуй